Medical Care in Emergency Units with Risk Classification: Time to Attendance at Hospital based on Parametric Models - Ramos, Pedro L.; Nascimento, Diego C.; Fernandes, Robson; Guimarães, Edson; Santana, M.; Soares, Kleber; Louzada, Francisco (Trends in Computational and Applied Mathematics, 2019)
The present work intends to study the effectiveness of applying Manchester Triage System to improve patient flow in a Brazilian hospital, which allow a more welcoming and decisive service.  Thus, time to event techniques are applied based on parametric regression models with the objective of investigating indicators for the emergency/urgency sector and thus, contributing to better operational efficiency. The results show that different explanatory variables such as classification, age, period, among others, influence in the time of attendance. At the end, we provide a simple model that can be used to predict such time under different explanatory variable for a particular Brazilian hospital.